Importance of argumentation in criminal proceedings - Bibilo, Valentina N. (Journal of the Belarusian State University. Law, 2019)
The article considers the concept of argumentation and its importance in criminal proceedings. The author reveals the specifics of argumentation at the pre-trial and trial stages of the criminal proceedings. It is shown that one of the integral features of the argumentation is its persuasive effect on the subjects. Argumentation penetrates the entire contents of the criminal proceedings and manifests itself through legality, validity, motivation and fairness of the judgment.